Relación de las dinámicas familiares con el desempeño escolar en estudiantes de 8° de bachillerato de una institución educativa del Distrito de Riohacha. (2024)
The purpose of this research is to describe the relationship between family dynamics and school performance in 8th grade high school students at the GARDNER Institute of the Riohacha District. The sample included 14 8th grade high school students from the selected educational institution in the District of Riohacha. A descriptive methodology with a correlational approach was used, combining a quantitative approach. A structured questionnaire was administered to collect data on family characteristics and the level of support received from parents, to obtain a more detailed understanding of family dynamics and their influence on school performance.